2015
DOI: 10.3109/14756366.2015.1096270
|View full text |Cite
|
Sign up to set email alerts
|

Salts of 5-amino-2-sulfonamide-1,3,4-thiadiazole, a structural and analog of acetazolamide, show interesting carbonic anhydrase inhibitory properties, diuretic, and anticonvulsant action

Abstract: Three salts of 5-amino-2-sulfonamide-1,3,4-thiadiazole (Hats) were prepared and characterized by physico-chemical methods. The p-toluensulfonate, the methylsulfonate, and the chlorhydrate monohydrate salts of Hats were evaluated as carbonic anhydrase (CA, EC 4.2.1.1) inhibitors (CAIs) and as anticonvulsants and diuretics, since many CAIs are clinically used as pharmacological agents. The three Hats salts exhibited diuretic and anticonvulsant activities with little neurotoxicity. The human (h) isoforms hCA I, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
(62 reference statements)
1
11
0
Order By: Relevance
“…Among the wide range of heterocycles studied to develop pharmaceutically significant molecules, 1,3,4-thiadiazole has played a significant role in medicinal chemistry. Moreover, 1,3,4-thiadiazole nucleus has fascinated significance in medicinal chemistry, displaying pharmacological properties such as, antimicrobial [8][9][10] , anti-inflammatory 11 , antitumor 12,13 , anticonvulsant 14,15 , antioxidant 16 , antifungal 17 , antitubercular 18 , and antidepressant activities 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the wide range of heterocycles studied to develop pharmaceutically significant molecules, 1,3,4-thiadiazole has played a significant role in medicinal chemistry. Moreover, 1,3,4-thiadiazole nucleus has fascinated significance in medicinal chemistry, displaying pharmacological properties such as, antimicrobial [8][9][10] , anti-inflammatory 11 , antitumor 12,13 , anticonvulsant 14,15 , antioxidant 16 , antifungal 17 , antitubercular 18 , and antidepressant activities 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The shift of pH value to 8.0-8.5 (low alkali) was observed in urinalysis groups treated with 2a, 2c, 2e compared to the intact animals where the pH was 7.1. Such pH shift is a typical pharmacokinetic feature for 1.3.4-thiadiazol-bearing diuretics [21][22][23]. No negative changes such as appearance of glucose, protein, nitrite, occult blood in urine, or increasing specific gravity value were observed under the treatment with 2a, 2c, 2e.…”
Section: Diuretic Activitymentioning
confidence: 84%
“…The modified 1,3,4-thiadiazole nucleus is known as a scaffold for the design of potent derivatives with diuretic action [16][17][18][19]. The acetazolamide and methazolamide ( Fig.1) present widely used diuretic drugs with 1,3,4-thiazdiazole core belong to the carbonic anhydrase inhibitors (CAIs) [20][21][22][23].…”
Section: Bioorganic Chemistrymentioning
confidence: 99%
“…tosylate protein. It concluded that 5-amino-2-sulfonamide thiadiazole showed 72%-79% protection at 90 mg/kg against both the standard used when compared with its synthesized salts with no neurotoxicity; good binding affinity toward the selected protein by inhibiting carbonic anhydrase was also observed and was found effective against mild convulsions (Diaz et al, 2016).…”
Section: 34-thiadiazole Derivatives As Anti-convulsantmentioning
confidence: 99%